Digital Transformation Strategy for MSMEs to Increase Competitiveness: An Indonesian Case Study - Santoso, Cahyo Budi; Laksniyunita, Wanda; Sitompul, Gabriel Amadeus; Hamdany, Mohammad Azharie; Lestari, Eko Budi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the digital transformation strategies of MSMEs to increase competitiveness: A Case Study of Indonesia. This study uses a descriptive qualitative approach with a case study design to explore the digital transformation strategies of MSMEs in Indonesia. Data were collected through in-depth interviews, participant observation, and documentation. Then, they were analyzed using data reduction, data presentation, and conclusion drawing. The results show that the digital transformation strategy involves three main aspects: marketing, operations, and human resource development. MSMEs utilize social media and marketplaces to expand their markets and increase sales. The application of technology to operational aspects, such as digital recording and stock management, helps improve business efficiency and accuracy, while human resource development through training accelerates the digital adaptation process. However, this transformation still faces challenges such as limited infrastructure, low digital literacy, limited human resources and finances, and data security. Therefore, support from the government, the private sector, and the community is needed to create an inclusive digital ecosystem.